Lack of Augmenter of Liver Regeneration Disrupts Cholesterol Homeostasis of Liver in Mice by Inhibiting the AMPK Pathway. Issue 8 (2nd June 2020) - Wang, Xin; Dong, Ling‐yue; Gai, Qu‐jing; Ai, Wei‐lun; Wu, Yuan; Xiao, Wei‐chun; Zhang, Jing; An, Wei
Abstract : It is well known that excessive cholesterol accumulation within hepatocytes deteriorates nonalcoholic fatty liver disease (NAFLD). Augmenter of liver regeneration (ALR) has been reported to alleviate NAFLD through anti‐apoptosis; however, whether ALR could protect liver from cholesterol‐induced NAFLD remains unclear. Mice with heterozygous deletion of Gfer (the gene for ALR, Gfer +/− ) were generated, and liver steatosis was induced by either choline‐deficient ethionine‐supplemented, methionine choline–deficient diet for 4 weeks, or high‐fat diet for 16 weeks. The results showed that Gfer +/− mice developed a more severe fatty liver phenotype than Gfer +/+ mice. The livers of Gfer +/− mice exhibited a higher concentration of cholesterol and low‐density lipoprotein compared with the normal mice. Transcriptome‐based analysis predicts low‐density lipoprotein receptor (LDLR) primarily involved in the metabolic pathway. The experiments further indicate that cholesterol accumulation within hepatocytes is closely associated with enhancing the expression of LDLR and activation of sterol regulatory element binding protein 2 (SREBP2). Because adenosine monophosphate–activated protein kinase (AMPK) is a critical regulator of SREBP2 activation, we measured whether the activity of AMPK was regulated by ALR. We found that knockdown of ALR expression inhibited the phosphorylation of LKB1, an upstream activator of AMPK, followed by AMPK inactivation and SREBP2 maturation/nuclear translocation, leading to extensive cholesterol accumulation. Meanwhile, cellular oxidative stress increased as a result of ALR knockdown, indicating that ALR might also have a role in suppressing reactive oxygen species production. Conclusion : Our results confirm that ALR regulates cholesterol metabolism and alleviates hepatic steatosis probably through the LKB1‐AMPK‐SREBP2‐LDLR pathway in vivo and in vitro, providing a putative mechanism for combating fatty liver disease. Abstract : ALR knockdown promotes cholesterol deposition in hepatocytes. ALR knockdown regulates the LKB1‐AMPK‐SREBP2‐LDLR pathway. Replacement of ALR gene into Gfer +/‐ mouse primary hepatocytes can promote AMPK activation, rescuing hepatocytes from cholesterol deposition.